Flexural Strengthening of Reinforced Concrete Beams with Substandard Tension Lap Splices Using a Novel Pre-stressing Technique - Roba Osman; Ahmed Elkhouly; Boshra Eltaly; Mohamed H. Zakaria (International Journal of Concrete Structures and Materials)
Abstract Sudden failure of reinforced concrete (RC) beams with substandard tension lap splices due to low resistance to flexure is a critical issue that needs to be addressed. Accordingly, a novel pre-stressing technique is presented in this paper, which offers a promising solution for strengthening RC beams with substandard tension lap splices. The technique involves the use of external steel bolts, load-transferring brackets, and bearing plates. Eleven test specimens sized 100 × 200 × 1500 mm3 were utilized in a series of experimental investigations to assess the effectiveness of the suggested approach. These specimens consisted of one specimen without a tension lap splice, one with a sufficient tension lap splice equal to 60d b, and nine beams with insufficient tension lap splices equal to 25d b. The investigation considered three main variables for eight strengthened specimens: the length of the strengthening plate (L s = 60d b, 80d b, and 100d b), the number of bolts (N b = 2, 3, and 4 pairs), and the pre-stress level in the bolts (PL = 0.1f y, 0.2f y, and 0.3f y). The effects of the proposed strengthening technique on ultimate load (P ult), first cracking load (Pc), deformation behavior, failure pattern, cracks distribution, deflection ductility, flexure toughness, and elastic stiffness were investigated. The findings demonstrated that the pre-stress approach considerably enhanced the ultimate load (61.52–218.65%) and first crack load (80.15–106.40%) of the strengthened specimens compared with the control specimen. In addition, there was a notable improvement in flexural toughness and elastic stiffness, with an average value of 205.5% and 101.35% for all strengthened specimens, respectively. Also, strengthened RC beams showed considerable improvements in ductility, with an average increase in peak (μ p) and ultimate deflection (μ uf) indices of 120.16% and 94%, respectively. In general, the novel pre-stressing technique enhances the structural performance of the beams by increasing their load-carrying capacity, improving ductility, and enhancing crack resistance.